Pengarsipan Berbasis Dokumentasi Media Sosial “Gendis Sewu” dalam Perspektif Maqasid Syariah - Rachman, Rio Febriannur; Ghulam, Zainil (Program Study Office Adminstrative of Akademi Komunitas Teknologi Syarifuddin Lumajang, 2023)
This article discusses one of the public policies implemented by the Surabaya Library and Archives Service. This policy takes the form of documentation-based archiving on social media which is carried out in the Gendis Sewu program. The social media platforms used are websites, YouTube, and an application called